Possibilities of Ultrasound Diagnostics of Urolithiasis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Urolithiasis (UCD) is one of the most common urological diseases and ranks second in the world after inflammatory nonspecific diseases of the kidneys and urinary tract. Its share among all urological diseases is about 40%. In 70% of patients, ICD is diagnosed at the age of 30–60 years, and there is a predominance of males. The increase in morbidity, the severity of complications, the tendency to relapse, and the predominant affection of young and most able-bodied people make the diagnosis and treatment of nephrolithiasis one of the most important problems of urology. Urolithiasis is a metabolic disease caused by various exogenous and/or endogenous factors, often has a hereditary nature and is determined by the presence of a calculus in the urinary system.